STUDY OF SUPPRESSION OF HIV VIRAL LOAD AMONG PEOPLE RECEIVING ANTIRETROVIRAL THERAPY IN PALEMBANG CITY - Adeleine Silva Vanessa; Rico Januar Sitorus; Najmah Najmah (Jurnal Berkala Epidemiologi)
Background: Suppression of viral load is a targeted strategy for the prevention of HIV transmission. Viral load (VL) testing can be done at all health centres in Palembang City with free services. Purpose: This study aims to evaluate VL suppression and factors associated with VL suppression. Methods: The study design of this research was a cross-sectional study with data analysis using the Chi-square and binomial logistic regression tests. The population in this study was all HIV patients who accessed health services for VL testing. Data sources were obtained from the HIV/AIDS Information System (SIHA) for the period 2023 - June 2024. Results: The majority of PLHIV cases were male (1072 people) (83%) and unmarried (802 people) (62.1%). The transmission group was male-sexual males, 54.88%, with an average age of 36.62 years. The results of multivariate analysis showed that there were three variables associated with viral load levels, namely age with a p-value <0.03, AOR = 1.59 (95% CI: 1.04-2.43), ARV adherence with a p-value < 0.00, AOR = 1.76 (95% CI: 1.18-2.61), and clinical stage with a p-value < 0.04 AOR = 1.02 (95% CI: 1.02-2.07). Conclusion: Adherence to ART therapy, prevention of opportunistic infections, and early detection of clinical stage are predictors of successful viral load suppression. The role and responsibility of the community and the active participation of health workers in early detection, treatment and care are needed.